Complications related to elective generator replacement of the subcutaneous implantable defibrillator. Issue 3 (16th November 2020) - van der Stuijt, Willeke; Quast, Anne-Floor B E; Baalman, Sarah W E; de Wilde, Koen C; Brouwer, Tom F; Wilde, Arthur A M; Knops, Reinoud E
Abstract: Aims: To guarantee uninterrupted function of the subcutaneous implantable cardioverter-defibrillator (S-ICD), the pulse generator needs to be surgically replaced before the battery is depleted. The risks related to this replacement substantially impact long-term outcome for S-ICD recipients, as the majority will undergo one or several of these procedures in their lifetime. We aim to describe the procedural characteristics of the replacement procedure and to provide an insight in the complications associated with these replacements. Methods and results: In this retrospective analysis, data from replacement procedures and follow-up visits were collected from all patients who underwent elective S-ICD generator replacement in our tertiary centre from June 2014 until November 2019. Original device position was assessed using the PRAETORIAN score. Complications were defined as those requiring surgical intervention, systemic antibiotic treatment, or device extraction. Seventy-two patients were included, with a median follow-up of 1.9 years (IQR 0.6–3.3 years) after replacement. Battery depletion occurred after 5.9 ± 0.7 years. The pulse generator was repositioned in patients with a PRAETORIAN score ≥90 to minimize the defibrillation threshold. Although there was an increase in impedance compared to the implant procedure, first shock conversion rate during defibrillation testing was 91.4% with a success rate of 100% after multiple attempts. Two patients developed a complication after, respectively, 9 and 21 months, resulting in a complication rate of 1.4% per year. Conclusion: With a median follow-up of 1.9 years, this study shows a low complication rate after S-ICD replacement, with a first shock conversion rate of 91.4%.